Discrete event simulation for health technology assessment - Caro, J. Jaime; Møller, Jørgen; Karnon, Jonathan; Stahl, James; Ishak, Jack (Online access with DDA: Askews (Medicine), 2016)
Discover How to Apply DES to Problems Encountered in HTADiscrete event simulation (DES) has traditionally been used in the engineering and operations research fields. The use of DES to inform decisions about health technologies is still in its infancy. Written by specialists at the forefront of this area, Discrete Event Simulation for Health Techno.